Teachers’ Self-Efficacy: The Role of Personal Values and Motivations for Teaching - Barni, Daniela; Danioni, Francesca; Benevene, Paula (Frontiers in Psychology, 2019)
Teachers’ personal values drive their goals and behaviors at school. Moreover, values can support subjective well-being and an individual sense of self-efficacy. Teachers’ self-efficacy, namely teachers’ beliefs in their ability to effectively handle the tasks, obligations, and challenges related to their professional activity, plays a key role in influencing important academic outcomes (e.g. students’ achievement and motivation) and well-being in the working environment. Based on Schwartz’s well-known theory of human values, this study sought to examine the relations between teachers’ values (i.e. conservation, openness to change, self-transcendence, self-enhancement) and their self-efficacy. In particular, it aimed at analyzing the extent to which these relations are moderated by teachers’ controlled and autonomous motivations for teaching. Two hundred and twenty-seven Italian high school teachers (73.6% females; M = 44.77 years, SD = 10.56) were involved in the study and asked to complete a self-report questionnaire. Results showed that teachers’ conservation values were positively associated to sense of self-efficacy regardless of the type and level of motivation for teaching. More interestingly, the relationships between openness to change and self-efficacy on the one hand, and self-transcendence and self-efficacy on the other, varied depending on teachers’ motivations. These relations were stronger when teachers perceived less external pressure and felt to be self-determined toward teaching. Implications of these results for teachers’ practices and well-being in their work environment and further developments of the study are discussed.